2008
DOI: 10.1111/j.1600-079x.2008.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation products of melatonin derivatives exhibit acetylcholinesterase and butyrylcholinesterase inhibitory activity

Abstract: It is already well documented that melatonin exhibits strong antioxidant properties. It traps several reactive oxygen species including singlet oxygen, peroxyl and hydroxyl radicals. Also, peroxynitrite-induced reactions are inhibited by melatonin. The oxidation of melatonin by singlet molecular oxygen [O(2) ((1)Delta(g))] may produce cyclic 3-hydroxymelatonin whose structure we have already studied. In this investigation we report on the synthesis of several melatonin analogues having a carbamate substituent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The function of cholinesterase inhibitors (ChEIs) is to increase the endogenous levels of acetylcholine (ACh) in the brains of AD patients, eventually increasing cholinergic neurotransmission. It is not surprising that ChEIs have shown better results in the treatment of AD than any other strategy explored; for example, compounds having a 2,3,8,8a-tetrahydropyrrolo[2,3-b]indole heterocyclic system, a characteristic structural motif of alkaloids such as physostigmine and phenserine, are considered potent ChEIs for use in AD treatment [11]. Both ChEs show a characteristic cleft intruding into the enzyme surface, containing the catalytic triad and choline binding sites where ACh is cleaved.…”
Section: Introductionmentioning
confidence: 99%
“…The function of cholinesterase inhibitors (ChEIs) is to increase the endogenous levels of acetylcholine (ACh) in the brains of AD patients, eventually increasing cholinergic neurotransmission. It is not surprising that ChEIs have shown better results in the treatment of AD than any other strategy explored; for example, compounds having a 2,3,8,8a-tetrahydropyrrolo[2,3-b]indole heterocyclic system, a characteristic structural motif of alkaloids such as physostigmine and phenserine, are considered potent ChEIs for use in AD treatment [11]. Both ChEs show a characteristic cleft intruding into the enzyme surface, containing the catalytic triad and choline binding sites where ACh is cleaved.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, several derivatives of c3OHM have been synthesized and investigated for inhibition of acetyland butyrylcholinesterase activities [127]. This might be of value with regard to the assumed possibility of interfering with the progression of Alzheimer's disease by inhibiting the acylcholinesterases.…”
Section: Non-enzymatic Hydroxylation and Nitro-sationmentioning
confidence: 99%
“…The original N ‐acetylserotonin 5 was obtained by the acetylation of serotonin, according to the procedure described in our previous work [12]. Coupling of compound 5 with ethyl isocyanate, in the presence of catalytic amount of sodium, afforded a carbamate derivative 6 in 57% yield.…”
Section: Methodsmentioning
confidence: 99%
“…We have already described the synthesis of compound 9 [12] but we found that the singlet oxygen–induced cyclization gave better results when tetraphenyl porphyrin was used as a photosensitizer. Mild methanolysis in the presence of sodium methoxide, followed by the removal of the silyl protecting group, gave a stable compound 10 , which may serve as a substrate for various O ‐acylations at the phenolic moiety.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation